Empathetic Space on Screen Constructing Powerful Place and Setting - D'Adamo, Amedeo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2018)
In this book we learn that there is a clear but complex relationship between setting and character on screen. Certain settings stand out above others$1 (Bthink of the iconic gooey dripping tunnels that Ripley stumbles through in Aliens, Norman$1 (Bs bird-decorated parlour in Psycho or the dark Gotham of certain Batman movies. But what makes these particular settings so powerful and iconic? Amedeo D$1 (BAdamo explains why we care about and cry for certain characters, and then focuses on how certain places then become windows onto their emotional lives. Using popular case studies such as Apocalypse Now, Amelie, Homeland and The Secret Garden, this original and insightful book is the first to really explain what makes some settings so effective, revealing an important but as yet uncovered machinery of empathy in visual narrative space. An invaluable resource for students, academics and indeed young filmmakers designing their very own narratives for space on screen.s
PART I : THE BUILDING CODES OF NARRATIVE SPACE -- 1. Introduction : Welcome to Dantean Space. Empathy and Space in Singin' in The Rain, Legally Blonde, The Pursuit of Happyness and Aliens -- 2. The Empty Man Of Action VS The Active Heart : DisPassionate & Dramatic Characters from James Bond and Sherlock Holmes to Little Miss Sunshine, Hamlet and The Hobbit -- 3. The Frozen Ones : Dantean Moments, Characters & Space from Aliens to Amelie, Sunset Blvd, Batman and others -- 4. Are We Empathizing with the Situation or With The Character? : A Methodology of Defining Space and Character in films like Little Miss Sunshine, 50 Shades Of Grey, Twilight & Secretary and TV shows like Lego Friends -- PART II : BOUNDARIES VISIBLE AND BROKEN -- 5. The Library of All Stories : Purgatory, Therapy and Character Arcs in Dante and in Great Expectations, One Hour Photo, The Third Man and Sunrise, in Camus' novel The Fall, and in Edgar Allen's Poe's short stories -- 6. Ghosts and Shades and Place : Empathetic Hauntology in Gravity, Lars and The Real Girl & Hiroshima Mon Amour -- 7. On Collapsing Boundaries between Protagonist and Antagonist : Dante's tricks and others in La Vie En Rose and Apocalypse Now and in the documentaries Tarnation, Elena and Waltzing With Bashir -- 8. Alienated Spaces : DeathStarchitecture, Showroom Space and the Dantean Homes of Homeland, Star Wars, Mad Men and The Graduate -- PART III : HOW NOT TO THINK LIKE DANTE ALIGHIERI : THE SOCIAL IMPLICATIONS OF DANTEAN SPACE -- 9. How Not To Think Like Dante Alighieri : Guilt, Punishment & the components of Dantean Space.-10. Escaping Dantean Space : On Creating Zones of Care in the biography of St Teresa, in physical materials and through Cinematography -- 11. How To Create Ecstatic Space : On crafting Zones of Care in Literature, Cinema and VideoGames in the films Amelie & The Secret Garden and in the videogame Wrath Of The White Witch.
Keywords: Culture$1 (BStudy and teaching.s; Motion pictures; Motion pictures$1 (BUnited States.s; Motion pictures -- Production and direction; Motion picture authorship; Popular Science in Cultural and Media Studies; Film Theory; American Cinema and TV; Film and TV Production; Screenwriting